2005
DOI: 10.1892/0891-6640(2005)19[515:dwhdct]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Dogs with Heart Diseases Causing Turbulent High-Velocity Blood Flow Have Changes in Platelet Function and von Willebrand Factor Multimer Distribution

Abstract: The purpose of this prospective study was to investigate platelet function using in vitro tests based on both high and low shear rates and von Willebrand factor (vWf) multimeric composition in dogs with cardiac disease and turbulent high-velocity blood flow. Client-owned asymptomatic, untreated dogs were divided into 4 groups: 14 Cavalier King Charles Spaniels (Cavaliers) with mitral valve prolapse (MVP) and no or minimal mitral regurgitation (MR), 17 Cavaliers with MVP and moderate to severe MR, 14 control do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This hypothesis was partly derived from a publication evaluating the effects of turbulent high-velocity blood flow on platelet function in dogs with mitral valve insufficiency. 24 In these dogs, platelet dysfunction was apparent as prolonged PFA-100 closure times and accompanied by decreased circulating large vWf multimers, suggesting that turbulent blood flow or high shear conditions may enhance proteolysis of more functional multimers by ADAMTS-13, leading to a qualitative loss of function. We did not measure specific multimeric structures, nor did we investigate the presence of qualitative abnormalities in this study, but this may be of interest for further characterizing the impact of HWI on vWF.…”
Section: Ta B L Ementioning
confidence: 84%
“…This hypothesis was partly derived from a publication evaluating the effects of turbulent high-velocity blood flow on platelet function in dogs with mitral valve insufficiency. 24 In these dogs, platelet dysfunction was apparent as prolonged PFA-100 closure times and accompanied by decreased circulating large vWf multimers, suggesting that turbulent blood flow or high shear conditions may enhance proteolysis of more functional multimers by ADAMTS-13, leading to a qualitative loss of function. We did not measure specific multimeric structures, nor did we investigate the presence of qualitative abnormalities in this study, but this may be of interest for further characterizing the impact of HWI on vWF.…”
Section: Ta B L Ementioning
confidence: 84%
“…Previous research also has found associations between platelet count and platelet aggregation response in CKCS using various methodologies. Some found that low platelet count in CKCS was associated with a more hypercoagulable pattern, 36 others found that platelet count was positively associated with aggregation response 9 and no association between platelet count and aggregation response also has been reported 37,38 . Approximately one third of CKCS have inherited macrothrombocytopenia, which usually is not associated with clinical signs of disease 25,28,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Some found that low platelet count in CKCS was associated with a more hypercoagulable pattern, 36 others found that platelet count was positively associated with aggregation response 9 and no association between platelet count and aggregation response also has been reported. 37,38 Approximately one third of CKCS have inherited macrothrombocytopenia, which usually is not associated with clinical signs of disease. 25,28,39 The reason for including the echocardiographic variable LV FS among variables with possible influence on basal aggregation and the effect of pimobendan on aggregation response is that a previous study indicated that increasing LV FS was associated with hypercoagulability based on thromboelastography in CKCS.…”
Section: Association Between Basal Platelet Aggregation Response and ...mentioning
confidence: 99%
“…During the progression of CHF, turbulent high velocity blood ow and changes in blood shear stress around the degenerative mitral valve lea ets may produce platelet activation in dogs (4,5). Although clinical relevance of the platelet activation is not clear (6), some studies in this species have shown that activated platelets might contribute to the disease progression and an increased risk of sudden death by development of intra-myocardial coronary arteriosclerosis and micro-thrombi due to CHF (4-8). Therefore platelets may play an important role in development and progression of cardiovascular diseases (CVDs) in dogs with or without overt-thromboembolism (7) as occurs in humans (9).…”
Section: Introductionmentioning
confidence: 99%